Bimbingan Teknis Aplikasi Pelaporan Buku Pokok Pemakaman Disdukcapil Kabupaten Pringsewu - Bintoro, Panji; Zulkifli; Ratnasari, Ratnasari; Andika, Tahta Herdian; Setiawan, Agustinus Eko; Aras, Irsan (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: The Population and Civil Registration Office is a governmental institution responsible for managing population administration in provinces or districts/cities. One of the tasks of the Population and Civil Registration Office is to provide services for death reporting, particularly in Pringsewu Regency. Currently, the death-reporting service system still operates manually. Methodology/approach: This challenge arises from the slowness of death-reporting services. Therefore, socialization regarding the protection of death certificates and the reporting of funeral registers has been conducted to facilitate and improve the reporting of funeral registers, especially in the administrative region of the Department of Population and Civil Registration of the Pringsewu Regency. The method used in the implementation of death certificates and funeral register reporting starts from the preparation stage, technical application guidance stage, and final stage, which involves affirming the commitment to implement the knowledge gained during the technical guidance process. Results/findings: This application was designed with a simple layout to facilitate the use of death certificate services and to report the main burial book. By entering relevant sections, users can directly access relevant applications. Limitations: In serving the community at the Population and Civil Registration Office of Pringsewu Regency, there is a limitation, namely, the Funeral Register Reporting application is built based on a website platform that can be utilized across multiple platforms. Contribution: The contribution to community services involves designing, constructing, and directly implementing the Funeral Register Reporting application for relevant stakeholders in Pringsewu Regency. Consequently, the developed application proved to be highly beneficial and helpful for the stakeholders involved.